Handbook of research on managerial practices and disruptive innovation in Asia - Ordóñez de Pablos, Patricia 1975-; Zhang, Xi 1982-; Chui, Kwok Tai (IGI Global, 2020)
"This book explores emerging topics, challenges, and success factors in management, disruptive innovation, and inclusive economies in Asia"--
Description based on title screen (IGI Global, viewed 09/12/2019)
Keywords: Management; Technological innovations / Economic aspects; Technological innovations / Economic aspects / Asia; Management / Asia